NEXT-GENERATION SEQUENCING AND IMAGING FLOW CYTOMETRY ANALYSIS OF THE MICROBIAL COMMUNITIES OF ARAL SEA REMNANT LAKES - Askerov, Alyamdar (School of Sciences and Humanities, 2023)
Once one of the largest lakes by area, the Aral Sea’s water level decreased drastically within the last 60 years due to climate change and anthropogenic activity. This resulted in the emergence of several distinct saline and hypersaline water reservoirs, such as the Small Aral Sea, the West Aral Sea, and Chernyshev Bay. This study is focused on: 1) the characterization of the epilimnion phytoplankton and bacterioplankton communities of the Chernyshev Bay and northern parts of West Aral Sea, and 2) the correlation of phytoplankton and bacterioplankton biodiversity to the set of environmental variables (e.g., temperature, conductivity, salinity, pH, and nutrient concentration). To accomplish this, water samples were collected from the Chernyshev Bay and the West Aral Sea (expedition Aral-2022), which were further analyzed by full-length 16S rRNA next-generation sequencing (NGS) for bacterioplankton diversity, and imaging flow cytometry (IFC) for phytoplankton diversity. The obtained bacterioplankton diversity was further analyzed using alpha-diversity metrics via Shannon and Simpson indices and Non-metric MultiDimantional Scaling (NMDS tests). Lastly, the effect of enviroronmental parameters was analyzed using the Principal Component Analysis (PCA). According to the IFC results, Chernyshev Bay, but not the Western Aral Sea, was dominated in October 2022 by Dunaliella spp.(up to 98%), which confirms the final separation of Chernyshev Bay Lake. Several filamentous cyanobacteria, diatomic algae, and representatives of Aulacoseira, Aphanocapsa, and Pediastrum genera were detected in Chernyshev Bay’s water samples. NGS-based taxonomical analysis of bacteriome showed that there is a diversity dissimilarity between Chernyshev Bay and West Aral Sea and strong similarity among littoral and limnetic points within the Chernyshev Bay. According to the PCA result, conductivity and ammonium concentration were the most important environmental parameters. The patterns described here represent the first observation of bacteriome and phytoplankton distribution in Chernyshev Bay and West Aral parts of the former Aral Sea. The significance of this study is the contribution to our current knowledge of biodiversity in the Aral Sea, using a combined approach of NGS and IFC analysis. The obtained data can potentially enhance the limnological research of local and foreign hypersaline lakes across the globe.
Keywords: Type of access: Open Access; Aral Sea